2008
DOI: 10.2139/ssrn.1100131
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Power of Transparency in Context: Information's Role in Reducing Corruption in Uganda's Education Sector

Abstract: One of the popular stories told (and taught) in development circles is how corruption was slashed in Uganda simply by publishing the amount of monthly grants to schools. This paper takes a deeper look at the facts behind the Uganda story and finds that while information did indeed play a critical role, the story is much more complicated than we have been led to believe. A dramatic drop did occur in the percentage of funds being diverted from Uganda's capitation grant. But to attribute this leakage solely to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 6 publications
0
36
0
3
Order By: Relevance
“…Recent studies of social accountability have generated diverse and sometimes contradictory findings 1 about the kinds of supply-or demand-side strategies that might generate pro-poor outcomes in Uganda at the current juncture (Robinson, 2006;Hubbard, 2007;Reinikka and Svensson, 2004). The institutional framework for social accountability in Uganda has been shaped by both decentralisation policy and sector-specific reforms.…”
Section: Political Space For Social Accountability In Museveni's Ugandamentioning
confidence: 99%
“…Recent studies of social accountability have generated diverse and sometimes contradictory findings 1 about the kinds of supply-or demand-side strategies that might generate pro-poor outcomes in Uganda at the current juncture (Robinson, 2006;Hubbard, 2007;Reinikka and Svensson, 2004). The institutional framework for social accountability in Uganda has been shaped by both decentralisation policy and sector-specific reforms.…”
Section: Political Space For Social Accountability In Museveni's Ugandamentioning
confidence: 99%
“…Qualitative analysis after the impact evaluation showed that the effects were significant only in areas where community members were literate as well as assertive, since most other communities were bribed to not register complaints (Hubbard, 2007).…”
Section: Lessons Learnedmentioning
confidence: 99%
“…This implies that local elites in collaboration with political officials could co-opt the programme. In the case of the Ugandan programme, there was elite capture in places where the head teachers used their high status in the community to steal funds along with the local officials (Hubbard, 2007). Perception of corruption affects citizen response: A common perception amongst voters is that all politicians are corrupt to a certain degree.…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…(UNDP 2007: 172) 5 For a similar argument about mitigation see Ostrom (2010) 6 http://www.ccdare.org 7 Some the wider literature is reviewed in Booth (2011), Grindlee (2011, Centre for the Future State (2010), Rodrik (2007), North et al (2008), Acemoglu and Robinson (2008), and Leftwich (2008) 8 A series of public expenditure tracking surveys in the 1990s revealed how much money was going missing between legislatures approving expenditure centrally and its arrival at the point of delivery. In a particularly well-known case, almost 90% of funds voted for primary schools in Uganda in the early 1990s were being diverted (Hubbard 2007). 9 Much of the nature of African politics was formed in the relatively short period of independence from colonial rule, when nationalist leaders had to throw together coalitions extremely rapidly (Allen 1995).…”
Section: Conclusion and A Research Agendamentioning
confidence: 99%